PASSIVE DESIGNS AND THERMAL PERFORMANCE OF THE TEMPLES IN THE WARM-HUMID CLIMATIC ZONE OF SOUTH INDIA - Sarkar, Amitava; Panicker M , Jyothis (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Religious beliefs, traditional wisdoms, rituals, and cultural practices all play an important part in environmental and biodiversity protection. Conservation of environment and natural resources has long been an element of cultural ethics that can be observed in the vernacular architecture of India, practiced in different parts of the country. The Indian Temple architecture is a manifestation of these socio-cultural-environmental values which are conceptualized and constructed in unique ways integrating passive features which keeps on educating and inspiring generations after generations. These timeless Temples through their passive architectural elements and harmonic aesthetic qualities enable the societies to perceive themselves as part of a spiritual network and to connects them to their biophysical surroundings. Hence, the present research explores the passive architectural features and thermal performance of the naturally ventilated south Indian Temples, located in warm and humid climate zone, and how these passive features can be implemented in the present day’s buildings to achieve thermal comfort. The research deploys a qualitative descriptive comparative analysis method. It delves into case studies of two Temples located in Kerala, having warm-humid climate, to investigate the passive architectural features and thermal performance. Data collection is done through field visits to these two Temples: Iringole Kaavu Bhagavathy Temple (old) and Thottuva Temple (new). Measurements of environmental parameters are also collected during field-surveys. The study concludes that the adaptation of passive architectural features, in response to the local climatic conditions, are paramount and beneficial to improve the thermal performance of the structures and thermal comfort of the users. Hence, it is argued that the passive climate-responsive architectural features of the south Indian Temples, suitable to the local geoclimatic and cultural conditions, need to be continued to follow in the present and future generation of buildings.